PERANCANGAN SISTEM INFORMASI PEMESANAN TIKET PADA PT. SEJAHTERA - Grace Novita Sari Sihombing; Marlyna Infryanti Hutapea; Rena Nainggolan (Universitas Methodist Indonesia, 2021)
At this time information technology has evolved very rapidly and influential to all aspects of daily life, but ticket reservations generally still use a manual tool. The manual means that the ticket order still uses the ticket paper by filling up the data in writing and passengers must come directly to the counter to book a ticket. This is far from effective and efficient for passengers, frequent problems for potential passengers such as tickets that run out, a delayed departure hour or even a crowded bus. Hence, the writer raised the question of a hand-ordered ticket system. The goal of building this system is to make it easier for passengers to book tickets and to file administration for data processing. With this system in place, it is expected to solve previous problems and be useful to make bus reservations effective and efficient.